Modulated photochemical reactivities of O-acetylated (3', 5'-dimethoxyphenyl) heteroaryl acyloin derivatives under direct irradiation and photo-induced electron transfer conditions - Bisht, Rajesh; Singh, Saumya; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Photochemical & Photobiological Sciences, 2018)
3', 5'-Dimethoxybenzoin esters are important photoremovable protecting groups which form 2-phenylbenzofuran derivatives upon photo-release. We utilized a similar concept to test a photochemical method of installing a benzofuran moiety to the conjugated backbone by subjecting O-acetylated (3', 5'-dimethylphenyl) heteroaryl acyloin derivatives through direct photo irradiation and a photo-induced electron transfer reaction. These photochemical methods were explored for a variety of heteroaromatic substrates appended on the ketone part of the O-acetylated cross-acyloin derivatives. The furan, thiophene and bithiophene derivatives led to the expected cyclized (benzofuran capped) products but the derivatives with extended conjugation decomposed under direct irradiation. However, under irradiation in the presence of an electron donor such as triethylamine, the extended acyloin derivatives afforded both cyclized and deacetoxylated products. The semiconducting nature of the extended cyclized products was also explored and tested for solution-processed organic field effect transistors, providing a maximum hole mobility of 1.3 x 10(-6) cm(2) V-1 s(-1).

Modular TiO2-squaraine dyes/electrolyte interface for dye-sensitized solar cells with cobalt electrolyte - Singh, Ambarish Kumar; Sudhakar, Vediappan; Javaregowda, Bharathkumar H.; Bisht, Rajesh; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Chemphotochem, 2023)
Strategies to diminish both charge recombination and aggregation of dyes on the photoanode by functionalizing the sensitizer with alkyl groups is the best approach to achieve high dyesensitized solar cell (DSSC) efficiency. Development of such a photoanode with NIR-active dyes which is compatible with a cobalt electrolyte is important to enhance the photovoltaic performance. In this report, alkyl-group-wrapped donor-acceptor-donor (D-A-D) based unsymmetrical squaraine dyes have been used for DSSC device characterization with a cobalt electrolyte. Surface passivation of photoanode was varied systematically by the extent of functionalization with alkyl groups to avoid charge recombination. DSSC device performance of 5.92% was achieved for an alkyl-group-wrapped squaraine dye with a cobalt electrolyte. Hence, appending the alkyl groups on the donor unit of squaraine dyes helps passivating the photoanode, whereas introducing hydrophilic groups provides a leaky surface where oxidized electrolyte species reach the titanium-metal-oxide surface which promotes the charge recombination process.
Keywords: counter-electrode; DSSC device efficiency; Dye-sensitized solar cells; Electrolytes; unsymmetrical squaraine dye